Factors affecting the performance of retail Small - Medium Enterprise (SMEs) in Malaysia / Mohammad Hanafie Sazali and Amalina Nor Azhar - Sazali, Mohammad Hanafie; Nor Azhar, Amalina (Faculty of Business and Management, 2016)
Small and Medium Enterprises (SMEs) play an important part in economic growth in Malaysia. The increasing number of SMEs has led to an increase in aggressive competition among them. This made SMEs encountering more extreme challenge to have the capacity to keep up their presence and grow its business. Performance measure for SMEs is still not entrenched, like the performance measure in big organizations. This paper means to propose a conceptual structure for measuring the performance that can be utilized by SMEs. A few factors are proposed including effective entrepreneurship, human resource management, use of marketing information, and application of information technology (IT). The method used in this study is descriptive analysis with a survey conducts on Small and Medium Enterprises (SMEs) in Malaysia. This research is anticipated to contribute as the literature with regard to SMEs performance in the retail sector in Malaysia.